D-Mannose binding, aggregation property, and antifungal activity of amide derivatives of pradimicin A. (1st February 2022) - Miyanishi, Wataru; Ojika, Makoto; Akase, Dai; Aida, Misako; Igarashi, Yasuhiro; Ito, Yukishige; Nakagawa, Yu
Graphical abstract: Abstract: Pradimicin A (PRM-A) and its derivatives comprise a unique family of antibiotics that show antifungal, antiviral, and antiparasitic activities through binding to d -mannose (Man)-containing glycans of pathogenic species. Despite their great potential as drug leads with an exceptional antipathogenic action, therapeutic application of PRMs has been severely limited by their tendency to form water-insoluble aggregates. Recently, we found that attachment of 2-aminoethanol to the carboxy group of PRM-A via amide linkage significantly suppressed the aggregation. Here, we prepared additional amide derivatives (2 –8 ) of PRM-A to examine the possibility that the amide formation of PRM-A could suppress its aggregation propensity. Sedimentation assay and isothermal titration calorimetry experiment confirmed that all amide derivatives can bind Man without significant aggregation. Among them, hydroxamic acid derivative (4 ) showed the most potent Man-binding activity, which was suggested to be derived from the anion formation of the hydroxamic acid moiety by molecular modeling. Derivative 4 also exhibited significant antifungal activity comparable to that of PRM-A. These results collectively indicate that amide formation of PRM-A is the promising strategy to develop less aggregative derivatives, and 4 could serve as a lead compound for exploring the therapeutic application of PRM-A.